Identification of defense genes targeted by CRISPR-Cas systems in Acinetobacter baumannii. - Lupiáñez Almenara, Cristina; Pérez Pulido, Antonio J. (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2025)
Motivation: CRISPR-Cas systems are an acquired immunity system in bacteria and archaea, which allows them to recognise and degrade foreign DNA sequences. They do this thanks to short sequences they store in their genome, called spacers. Understanding which defense genes are recognised by these spacers may be of interest for understanding the phage fighting that often occurs in bacteria [1]. Building on a previous study in which the Acinetobacter baumannii pangenome was constructed and its spacers identified [2], this work aims to analyse the genes of other defense systems, out of the more than one hundred that the bacterium presents, which can be recognised by the CRISPR-Cas system. Methods: The A. baumannii pangenome was used and analysed with DefenseFinder v1.3.0 [3] to identify its defense genes. Subsequently, a similarity search was performed using the BLAST tool [4], configured to search for short fragments, between the identified genes and the previously obtained spacers. After analysing the results, the most abundant defense gene typologies were identified and a new BLAST analysis [4] focused on these genes was carried out to evaluate their recognition by CRISPR-Cas systems. Results: . Multiple genes from different defense systems recognized by CRISPR-Cas spacers were identified in A. baumannii. Among them, bacteriophage restriction-modification systems were prominent. Further analysis of these genes revealed a large sequence diversity among genes with the same annotation, not all of which were recognised as defense systems. However, some of these genes, belonging to phage sequences, showed a high level of recognition by spacers, suggesting a selective pressure on them. Conclusions:The results indicate that A. baumannii CRISPR-Cas systems are in part directed against phage defense genes, including restriction-modification systems. The large variability in the sequences of these genes suggests a continuous evolutionary race between phages and bacteria.